Review of the thermoluminescent dosimetry method for the environmental dose monitoring - Stanković-Petrović Jelena S. (VINCA Institute of Nuclear Sciences, 2021)
Passive solid state dosimeters, such as thermoluminescence dosimeters, provide integrated measurement of the total dose and are widely used in environmental monitoring programs. The objective of this paper is to provide a comprehensive review on the use of thermoluminescent dosimetry methods for monitoring radiation dose in the environment. The article presents the part of the research results of the project PREPAREDNESS (EMPIR 2016 call for Metrology for Environment joint research project) with a particular objective to harmonize procedures used by dosimetry services, relevant authorities and Institutes across the Europe. To achieve this, different monitoring routines that are based on passive environ mental dosimetry methods are investigated. Differences in performing specific steps such as preheating, reading, annealing, minimizing fading, and others, are analyzed. The investigation was performed by means of qualitative literature review that showed the lack of information about specific steps. The conclusion of this work is that thermoluminescent dosimetry measurement system has to be type-tested even though the testing procedure is complicated. In addition to this, control dosimeters should be introduced, International Organization for Standardization protocols should be followed during calibration, and finally, parameters influencing the measurement uncertainty have to be identified and well understood in order to pro duce ac cu rate dose measurement results.